Geochemical characteristics and origin of hydrocarbons in the Mesoproterozoic reservoirs in the Liaoxi Depression, NE China. Issue 2 (March 2020) - Tang, Youjun; Li, Meijun; Zhu, Qiuge; He, Daxiang; Jiang, Xingchao; Xiao, Hong; Shan, Junfeng; Kang, Wujiang; Leng, Junying; Wang, Wenqiang
Oil reservoirs have been discovered in the Mesoproterozoic strata in the Liaoxi Depression, NE China. In order to determine the source of oil shows of the Mesoproterozoic Gaoyuzhuang Formation and their organic geochemical characteristics, eight source rocks and reservoir cores from the Mesoproterozoic Gaoyuzhuang Formation and four source rocks from the overlying Middle Jurassic Haifanggou Formation were geochemically analysed. The distribution patterns of normal alkanes, acyclic isoprenoids, hopanes, steranes and triaromatic steroids of the Mesoproterozoic hydrocarbons from Well N-1 are consistent with those of source rock extracts from the Mesoproterozoic Gaoyuzhuang Formation in the Well L-1. The molecular marker compositions of source rock extracts from the overlying Middle Jurassic Haifanggou Formation are distinctively different from those of the Mesoproterozoic hydrocarbons. The results suggest that the Mesoproterozoic source rocks have significant petroleum generation potential. The Mesoproterozoic paleo-reservoir may be prospecting exploration targets in the Liaoxi Depression, NE China.